Comparison of gut-directed hypnotherapy and unspecific hypnotherapy as self-help format in children and adolescents with functional abdominal pain or irritable bowel syndrome: a randomized pilot study. Issue 12 (December 2017) - Gulewitsch, Marco D.; Schlarb, Angelika A.
Abstract : Objective: Psychosocial treatments for chronic abdominal pain in childhood or adolescence are effective, but time consuming and hardly available. In the present study, gut-directed hypnotherapy (GDHT) and unspecific hypnotherapy (UHT) were compared to evaluate the feasibility and efficacy of a hypnotherapeutic self-help intervention. Participants and methods: Children/adolescents between 6 and 17 years of age with chronic abdominal pain were randomized to GDHT or UHT. The treatment period was 12 weeks each. Measurements were performed before and after treatment. The primary outcome was a pain diary. Analysis was carried out as per protocol. Results: Of 45 participants included, 13 were lost to follow-up. Thirty-two participants (14 GHDT, 18 UHT) were analyzed. Dropouts had higher pain severity. Completers in both conditions showed good adherence and a similar decrease in days with pain and pain duration. Pain intensity decreased only in the UHT condition. Eleven participants (two GDHT, nine UHT) achieved clinical remission (>80% improvement) and 13 participants (seven GDHT, six UHT) improved significantly (30–80%). Conclusion: Results suggest a high efficacy of standardized home-based hypnotherapy for children/adolescents with abdominal pain. Children/adolescents with high pain severity are at risk of dropping out. The UHT condition showed slight evidence of superiority, but conditions were equivalent on most outcomes. Taken together, self-help approaches based on hypnotherapy could close a treatment gap and prevent chronification.